PV grid-connected information interaction methods based on public information modeling - Wu, Peng; Yu, Lei; Zhang, Ruifeng; Liu, Yinliang; Lin, Xinhao; Chen, Hang; Liu, Tong (Frontiers in Energy Research, 2024)
The grid integration of large-scale photovoltaic and other distributed energy sources is an effective solution for addressing power supply shortages and environmental pollution. However, the widespread adoption of photovoltaics and grid integration presents various technological and management challenges. To fulfill the demands of grid management and ensure safe operations, the exchange of information between different terminals is continuously escalating. Use of diverse communication standards creates the problem of "information islands" among terminals. Hence, a standardized information model is crucial for describing the photovoltaic grid integration business and enhancing the efficiency of related software platform research and development. This study extends the IEC 61970/61968 standards and presents a common information model for the integration of photovoltaic systems into the grid. Initially, the operational procedures for integrating photovoltaic systems into the grid are analyzed, and UML modeling tools are employed for business modeling purposes. Subsequently, leveraging the outcomes of the business modeling and the content of the IEC 61970/61968 standards, the development of the common information model is executed. Lastly, causal analysis is conducted along with the modeling of communication standard extensions specifically targeted for the integration of photovoltaic systems into the grid, culminating in the finalization of the construction of the common information model for photovoltaic grid connection.